THE THE CORRELATION BETWEEN STUDENTS’ HABIT OF WATCHING ENGLISH ANIMATED COMEDY MOVIES AND STUDENTS’ VOCABULARY MASTERY OF EIGHTH GRADERS IN SMPN 1 NGANTANG - Farkhi, Muhamad Reza; Munfaati, Farid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study explores the correlation between students' habits of watching English animated comedy movies and their English vocabulary proficiency among Eighth Graders at SMPN 1 Ngantang. The research involved 45 randomly selected students, and data collection employed questionnaires and vocabulary tests. The collected data underwent analysis using the Pearson Product Moment correlation. The findings indicate a significant but low negative correlation (r = -0.294) between students' movie-watching habits and their English vocabulary mastery. This correlation coefficient was smaller than the critical value at a 5% significance level. The two-tailed significance level (sig. = 0.05) further confirms a significant relationship between the variables. In conclusion, Eighth Graders at SMPN 1 Ngantang exhibit a significant but low negative correlation between their habits of watching English animated comedy movies and their English vocabulary mastery.